The Economic Value of European Organic Farming in the Transition to Climate Neutrality - Monica Laura Zlati; Costinela Fortea; Valentin Marian Antohi (Journal of Agriculture and Rural Development Studies, 2024)
Organic farming is a cornerstone of the European transition towards climate neutrality, offering sustainable solutions to reduce greenhouse gas emissions and promote a sustainable European food system. We aim to analyze the economic value of European organic farming based on a principal composites analysis to determine causal relationships and their effects between variables such as organic agricultural area, current expenditure on climate change mitigation, gross value added of organic farming, final energy consumption of agriculture and greenhouse gas emissions from agriculture. The results of the sutdi demonstrate that expanding the amount of organic agricultural land in operation and maintaining the investment process in green technologies and resources are closely linked to increasing the economic value of the sector and reducing environmental impacts. However, the significant variations in economic efficiency and pollution highlight the need to adopt appropriate policies and strategies to maximize the benefits of organic farming. The study is useful for European public policy makers to adjust current strategies on the transition to climate neutrality.